2006
DOI: 10.1029/2005jb004103
|View full text |Cite
|
Sign up to set email alerts
|

Transient, synobduction exhumation of Zagros blueschists inferred from P‐T, deformation, time, and kinematic constraints: Implications for Neotethyan wedge dynamics

Abstract: [1] We present the first P-T, deformation time, and kinematic constraints on the only known blueschist facies rocks (BS) present in the Zagros (Hajiabad area). The BS were underplated below the Sanandaj-Sirjan zone and crop out as kilometer-scale bodies within extensive colored melange units marking discontinuously the Neotethyan suture zone. P-T estimates point to high-pressure/low-temperature (HP-LT) conditions around 11 kbar and 520-530°C for the majority of BS, along a $15°C km À1 gradient. Some exotic blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
190
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 160 publications
(203 citation statements)
references
References 124 publications
(200 reference statements)
10
190
2
1
Order By: Relevance
“…The presence north of Shahr-e-Kord (the southern part of the SSZ) of metabasites, amphibolites and eclogites with mid-ocean ridge (MORB)-like compositions suggests remnants of Neo-Tethyan oceanic lithosphere (Davoudian et al 2006(Davoudian et al , 2007, thought to be exhumed subduction zone materials. Blueschists are an important component of SSZ rocks in the Haji-Abad area, where Agard et al (2006) documented metamorphic conditions around 11 kbar and 520-530 • C, and laser-ablation 40 Ar/ 39 Ar ages on phengite clustering at 85-95 Ma; similar rocks are found in the SSZ near Neyriz (Davoudian et al 2006(Davoudian et al , 2007. These blueschist occurrences show that some SSZ rocks were subducted and later exhumed.…”
Section: D Sanandaj-sirjan Zonementioning
confidence: 87%
See 4 more Smart Citations
“…The presence north of Shahr-e-Kord (the southern part of the SSZ) of metabasites, amphibolites and eclogites with mid-ocean ridge (MORB)-like compositions suggests remnants of Neo-Tethyan oceanic lithosphere (Davoudian et al 2006(Davoudian et al , 2007, thought to be exhumed subduction zone materials. Blueschists are an important component of SSZ rocks in the Haji-Abad area, where Agard et al (2006) documented metamorphic conditions around 11 kbar and 520-530 • C, and laser-ablation 40 Ar/ 39 Ar ages on phengite clustering at 85-95 Ma; similar rocks are found in the SSZ near Neyriz (Davoudian et al 2006(Davoudian et al , 2007. These blueschist occurrences show that some SSZ rocks were subducted and later exhumed.…”
Section: D Sanandaj-sirjan Zonementioning
confidence: 87%
“…In some of these models the SSZ is a continental fragment rifted from Arabia and was accreted to Eurasia during Cretaceous time (e.g. Glennie, 2000;Golonka, 2004;Agard et al 2005Agard et al , 2006. However, Robertson (2007) observed that the rocks of the SSZ cannot be correlated with Arabian rocks.…”
Section: D Sanandaj-sirjan Zonementioning
confidence: 99%
See 3 more Smart Citations